THE EFFECT OF DHIKR ON THE STRESS LEVEL AND BLOOD PRESSURE IN THE PATIENTS WITH HYPERTENSION AT PUSKESMAS GAMPING 1 - Finy Nur Annisafitri; Edy Suprayitno; Diyah Candra Anita K (P3M Universitas 'Aisyiyah Surakarta, 2022)
Hypertension can be prevented by pharmacological and non-pharmacological therapies. One of the non-pharmacological therapies is dhikr.Objective: The study aimed to know the effect of dhikr on stress level and blood pressure in patients with hypertension at Gamping 1 Public Health Center.Method: This research used Quasi experimental design.The sampling quota was 30 people. The Parametric statistical tests were sample dependent t-test and independent sample t-tets; and the non-parametric analysis were Wilcoxon and Mann Whitney.Results: The stress levels reduction in the intervention group was 5.80 with a P-value <0.05 (0.001), and the control group was -0.27 with a P-value> 0.05 (0.812). The decrease in systolic blood pressure in the intervention group was 21.14 mmHg, P-value <0.05 (0.000), and the control group was 4.00 mmHg, P-value> 0.05 (0.305). The decrease in diastolic blood pressure in the intervention group was 10.40 mmHg with a P-value <0.05 (0.000), and the control group it was 0.87 with a P-value> 0.05 (0.599).Conclusions and Suggestions: There is a reduction in stress levels and blood pressure in the patients with hypertension at Gamping 1 Public Health Center. Respondents are expected to do dhikr every day to reduce stress levels and blood pressure.